Peningkatan Literasi dan Pembentukan Karakter Sosial Melalui Pendekatan Masyarakat di Desa Cibatu Kabupaten Garut - Muhammad, Giantomi; Saepudin, Aep; Aldi, Muhamad; Dewi Wibowo, Lia Yulistia; Purnama, Dika; Ayu Syahrani, Nutfah; Meilana, Dariah (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The community approach is an effort to provide relevant education and socialisation to a homogeneous community. There are two efforts that must be made to the community in the midst of uncertain times, namely increasing community literacy and shaping social character. Literacy is an important part of developing community insight and knowledge. Social character is the basis for building networks and caring for one another. These two efforts were carried out by the community service group of the Faculty of Tarbiyah and Teacher Training, Islamic University of Bandung, through a community-based approach in Cibatu Village, Garut Regency. The aim of the activity was to improve literacy and shape social character through a community-based approach. The methods used in the implementation of the activity were interaction-based mentoring and socialisation. The steps taken were: 1) Identifying problems; 2) Planning activities and materials; 3) Coordinating activities; 4) Conducting socialisation; 5) Mentoring; 6) Monitoring and evaluation; and 7) Following up on the programme and documentation. The results of the activities show that the community is interested in improving literacy by reading books and responding to current issues with an objective perspective. Likewise, social character has been formed in relation to maintaining family relationships, caring for the environment, positive communication patterns, and spiritual attitudes in daily life.